Deformability of bends continuous three-span preliminary self-stressed steel concrete slabs - Hasenko, Anton (Academic journal Industrial Machine Building Civil Engineering, 2021)
Continuous steel reinforced concrete structures with the use of monolithic reinforced concrete slab as a compressed part of the section and steel profile part as stretched are widely used in civil building. However, the continuous monolithic reinforced concrete slab is uneven due strength to the different values of the support and span moments of the extreme and middle spans. The conducted experimental researches confirm expediency of the development of a two-stage method of manufacturing (concreting) of continuous multi-span monolithic reinforced concrete slab on fixed formwork (the first stage - concreting of the middle span; the second stage - concreting of the extreme spans) in order to balance the level of deflections in all spans slab. The proposed method allows to effectively use the load-bearing capacity of the continuous slab’s reinforcement with the same support installation step of the steel reinforced concrete floor.